Prospects of providing tourism services to national tourism facilities and international tourists in Surkhandarya region - Khudayberdiyeva Aynabad Rozimurodovna; Mamaraimova Hilola Abdukahhor's Qizi (Genius Journals, 2023)
The article explores the prospects of national tourism in the Surkhandarya region and providing tourism services to international tourists
Keywords: Surkhandarya region; national tourism; international tourists